Inclusive Math: Unlocking Potential for Special Needs Learners in Vocational Education; Study at SMK Negeri 2 Malang - Wulandari, Tri Candra; Khoiriyah, Wahyu Hanifatul; Faizah, Faizah; Azifatullatifah, Nadziroh; Alfaini, Nuvri; Ermawati, Eli (PT ARRUS Intelektual Indonesia, 2024)
The purpose of this research is to describe mathematics learning for students with special needs at SMK Negeri 2 Malang. This research is a qualitative research, which is analyzed descriptively. Researchers used interviews, observation and documentation in the data collection process. This research was conducted at SMK Negeri 2 Malang, which is located at 17 Veteran Street, Malang, Indonesia. The source of the interview was the inclusion class program coordinator, as well as the inclusion teacher at SMK Negeri 2 Malang. Researchers conducted in-depth interviews about the implementation of inclusive class learning at SMK Negeri 2 Malang. Observations were made in inclusive classes that were carrying out learning activities to observe learning methods, the media used, how teachers and students interacted and the use of learning resources. Researchers reviewed teaching module documents, lesson plans, forms of test questions, test results and reports on learning achievement of inclusion students. The validity of the research data uses the principle of method triangulation, namely by comparing data from interviews, observations and documents. Based on the results of interviews, observations and document reviews, mathematics learning activities for students with special needs are carried out separately from regular classes, the teaching teacher is an inclusion teacher, the media used is limited to a whiteboard, with lecture and question and answer methods. Observations show that inclusion students do not easily grasp the material that has been delivered by the accompanying teacher, requiring repetition 4 to 6 times. Math learning for SBK students is not carried out at the same time as the regular class, but is carried out in the study room, taught by the inclusion assistant teacher. The accompanying teacher does not use media during math lessons. SBK students have different difficulties in learning math concepts.